Market orientation, nonfinancial performance measures, and performance: evidence from Thailand / Sirilak Bangchokdee, Lokman Mia and Samkao Runglertkrengkrai - Sirilak, Bangchokdee; Mia, Lokman; Samkao, Runglertkrengkrai (Faculty of Accountancy, 2013)
The present study sought to examine the mediating effect of managerial use of nonfinancial performance measures in the relationship between market orientation and organizational performance. Data were collected from 203 departmental managers of medium to large hotels in Thailand. Path analysis was used to test the proposed hypothesis. The results indicate that market orientation is significantly related to the use of nonfinancial performance measures, and the use of nonfinancial performance measures is significantly associated with organizational performance. Thus, the use of nonfinancial performance measures plays a mediating role in the relationship between market orientation and organizational performance. An explanation for the results is that the use of nonfinancial performance measures can assist market-oriented Organisations to deliver products/services with superior value to meet customer needs and expectations, leading to improved organizational performance.